[Book Review] Hope Circuits: Rewiring Universities and Other Organizations for Human Flourishing by Jessica Riddell - Earle Abrahamson (Teaching & Learning Inquiry: The ISSOTL Journal)
Book review of Hope Circuits: Rewiring Universities and Other Organizations for Human Flourishing by Jessica Riddell.